(untitled) (Al-Mansour Journal, 2023)
Modern computer networks are increasingly being used to transmit multimedia traffic such as video and audio besides supporting traditional data communication applications require strong Quality of Services QoS constraints. However, network traffic is highly diverse and each traffic type has unique requirements in terms of bandwidth, delay, loss, and availability and with explosive growth of the Internet, most traffic has begun moving towards QoS routing techniques. In this research, an overview of the QoS routing problems is described through presenting the strengths and weaknesses points of routing strategies used for this problem. It is noted from the results of studying above points that there is an important problem appeared in QoS routing which is called the path-constrained path-optimization routing problem, so it is proposed a two iterative algorithms to solve this problem these are: DCLC-A (Delay Constraint Least Cost-First Iterative) and DCLC-B (Delay Constraint Least Cost-Second Iterative) that have a wide search to find the optimal path , From the experimental results of our two proposed algorithms, it is found that the DCLC-B gives the optimal path solution between two nodes.